The Hidden Power of “Thank You”: Exploring Aspects, Expressions, and the Influence of Gratitude in Religious Families - Joe M. Chelladurai; Loren D. Marks; David C. Dollahite; Heather H. Kelley; David B. Allsop (Psych, 2023)
Gratitude has been extensively studied over the past two decades. Among several predictors, aspects of religiosity and spirituality have been consistent predictors of gratitude. To explore the religious motivations and processes that foster the practice of gratitude, we undertook a systematic thematic analysis using interview data from a national qualitative project of 198 highly religious families. Participants (n = 476) included mothers, fathers, and children from various socioeconomic backgrounds and from diverse religious, racial, and ethnic backgrounds in the United States of America. Semi-structured interviews were conducted in the participants’ homes. Data for this study were analyzed using a team-based approach to qualitative analysis. The findings were organized thematically, including: (a) aspects of gratitude, (b) expressions of gratitude, and (c) the influence of gratitude. Two aspects of gratitude were identified: functional—what people were grateful for—and directional—to whom they were grateful. Expressions of gratitude involved participation in regular, gratitude-focused prayers and mutual day-to-day appreciation. The relational context and implications and context of gratitude in religious families were further examined and reported with sub-themes: (a) gratitude prompted positive re-evaluation of relationships and (b) gratitude reinforced religious faith. Implications, strengths, limitations, and future directions are discussed.